PERFORMANCE ANALYSIS OF CIVIL SERVANTS IN TAKOKAK DISTRICT CIANJUR REGENCY IN THE VILLAGE DEVELOPMENT PLAN - RANI ANDRIYANI; SAKTI ALAMSYAH; DARMO H SUWIRYO (CV KULTURA DIGITAL MEDIA, 2021)
In West Java, the performance of civil servants has been monitored by the e-Kinerja application which has been prepared by the West Java Regional Personnel Agency (BKD). Likewise in Cianjur Regency, the performance of civil servants can be measured through the SeKOCI application. The acceleration of development is important as the government's effort to reduce inequality and realize fair and equitable development so that the results can be felt by the whole community. The Developing Village Index (IDM) as a composite index formed from the Social Resilience Index (IKS), the Economic Resilience Index (IKE) and the Environmental Resilience Index (IKL) which provides basic data and information for village development, can be a measure of the success of a village. One of the villages with developing status is Pasawahan Village with an IDM value of 0.69. The performance of Civil Servants in Takokak District, Cianjur Regency needs to be improved as a form of responsibility and so that the village development planning process that is prepared can accommodate the needs of the community and move the community to become the main actors and movers in village development. The objectives to be achieved in this study are as follows: To determine the performance of Civil Servants in Takokak District, Cianjur Regency in the Village Development Plan. In this study, researchers used qualitative research methods. Based on the results of the study indicate that individual factors, psychological factors and organizational factors, the performance of Civil Servants in Takokak District is quite good, however, motivation is needed to further improve the abilities and expertise possessed, equalize perceptions to minimize conflicts, add Human Resources to avoid the occurrence of conflicts. overlapping, applying reward and punishment fairly, and establishing good working relationships to build organizational synergy.